The association of BTLA gene polymorphisms with non-small lung cancer risk in smokers and never-smokers - Andrzejczak, Anna; Partyka, Anna; Wiśniewski, Andrzej; Porębska, Irena; Pawełczyk, Konrad; Ptaszkowski, Kuba; Kuśnierczyk, Piotr; Jasek, Monika; Karabon, Lidia (Frontiers in Immunology, 2023)
Introduction: Lung cancer is the predominant cause of death among cancer patients and non-small cell lung cancer (NSCLC) is the most common type. Cigarette smoking is the prevailing risk factor for NSCLC, nevertheless, this cancer is also diagnosed in never-smokers. B and T lymphocyte attenuator (BTLA) belongs to immunological checkpoints which are key regulatory molecules of the immune response. A growing body of evidence highlights the important role of BTLA in cancer. In our previous studies, we showed a significant association between BTLA gene variants and susceptibility to chronic lymphoblastic leukemia and renal cell carcinoma in the Polish population. The present study aimed to analyze the impact of BTLA polymorphic variants on the susceptibility to NSCLC and NSCLC patients’ overall survival (OS). Methods: Using TaqMan probes we genotyped seven BTLA single-nucleotide polymorphisms (SNPs): rs2705511, rs1982809, rs9288952, rs9288953, rs1844089, rs11921669 and rs2633582 with the use of ViiA 7 Real-Time PCR System. Results: We found that rs1982809 within BTLA is associated with NSCLC risk, where carriers of rs1982809G allele (AG+GG genotypes) were more frequent in patients compared to controls. In subgroup analyses, we also noticed that rs1982809G carriers are significantly overrepresented in never-smokers, but not in smokers compared to controls. Additionally, the global distribution of the haplotypes differed between the never-smokers and smokers, where haplotypes A G G C A, C G A C G, and C G A T G were more frequent in never-smoking patients. Furthermore, the presence rs1982809G allele as well as the presence of rs9288953T allele (CT+TT genotypes) increased NSCLC risk in females’ patients. After stratification by histological type, we noticed that rs1982809G and rs2705511C carriers were more frequent among adenocarcinoma patients. Moreover, rs1982809G and rs2705511C correlated with the more advanced stages of NSCLC (stage II and III), but not with stage IV. Furthermore, we showed that rs2705511 and rs1982809 significantly modified OS, while rs9288952 tend to be associated with patients’ survival. Conclusion: Our results indicate that BTLA polymorphic variants may be considered low penetrating risk factors for NSCLC especially in never-smokers, and in females, and are associated with OS of NSCLC patients.